Methane oxidizing-plant growth-promoting yeast isolated from Indian rice fields - RANI, VIJAYA; BHATIA, ARTI; KAUSHIK, RAJEEV (The Indian Journal of Agricultural Sciences, 2021)
Potential methane-oxidizing-plant growth-promoting yeast was isolated and characterized during 2017-18 at the ICAR-Indian Agricultural Research Institute, New Delhi. Yeast isolates belonging to the genus Meyerozyma guilliermondii were isolated from five major flooded paddy growing regions of India. Among all the isolates, Meyerozyma guilliermondii KAS-143 efficiently oxidized methane up to 57.64% ± 0.83 in 6 d under in vitro conditions. It also produced a significant quantity of phytohormone IAA and solubilized P, K, and Zn. Meyerozyma guilliermondii KAS-143 can be used for devolving potential inoculants for flooded paddy which can not only promote plant growth but also simultaneously reduce methane emission by its oxidation.